Evaluation of a Push-Pull Approach for Aedes aegypti (L.) Using a Novel Dispensing System for Spatial Repellents in the Laboratory and in a Semi-Field Environment. - Ulla Obermayr; Joachim Ruther; Ulrich R Bernier; Andreas Rose; Martin Geier (PLoS ONE, 2015)
The increase in insecticide resistant mosquito populations necessitates the exploration of novel vector control intervention measures. Push-pull strategies for insect control have been successful when used in integrated crop pest management. Through the combinatory use of deterring and attracting stimuli, the abundance of insect pests can be changed in a given area. A push-pull strategy might also significantly reduce human-vector contacts and augment existing mosquito control strategies, e.g. through the combination of an attractive trapping system and a potent spatial repellent. Our approach includes the BG-Sentinel (BGS) trap in combination with catnip oil (Nepeta cataria), a known spatial repellent for Aedes aegypti. To impart a deterrent effect on mosquitoes at a distance, a homogenous and continuous dispersal of volatile repellent compounds is crucial. We have developed a repellent dispensing system that is easy to use and provides a homogenous dispersal of repellent in an air curtain. The use of five 9 V fans and custom-made repellent sachets containing 10% catnip essential oil created a repellent loaded air curtain that provided coverage of an area of 2 m2 (1.2 x 1.65 m). Air was sampled at four different heights in the curtain and analysed via thermal desorption (TD) and consecutive gas chromatography-mass spectrometry (GC-MS). Nepetalactone, the main constituent of the oil, was detected in air at a concentration range of 80 to 100 μg/m3 and the amounts were comparable at all four sampling positions. When a human volunteer was sitting behind the repellent curtain and a BGS trap was installed in front of the curtain in laboratory push-pull trials, Ae. aegypti landing collections decreased significantly by 50% compared to repellent-free controls. However, in a semi-field environment, comparable protective effects could not be achieved and further research on suitable repellent concentrations for outdoor implementation will be required.